Stressing to Breaking Point : Interpreting Stress Test Results - Worrell, Rupert (Washington, D.C. : International Monetary Fund, 2008)
This paper illustrates how stress tests of banking systems may be designed to evaluate banks' reaction to shocks of increasing intensity, up to the point where regulatory norms are breached, or banks become insolvent. This approach offers useful insight and guidance for regulatory policy and intervention, using existing methodology and data. The illustrations presented in this paper are a small sample of the wide variety of shocks, scenarios, and assumptions to which this approach may be applied.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet